Graduate teaching assistants' challenges, conflicts, and strategies for navigating COVID-19 - Acheme, Doris Ehi; Biwa, Valerie (Frontiers in Communication, 2023)
COVID-19 imparted unprecedented changes to higher education. Overnight, institutions were required to transition to online instruction, which brought about numerous challenges for instructors. This study examines the experiences of an often-overlooked instructor; graduate student assistants (GTAs). Their challenges and conflicts encountered with online instruction during COVID-19 and conflict management strategies are investigated. Sixteen (N = 18) GTAs from six universities in various regions of the United States were interviewed and constant comparative analysis was used to analyze data. Findings revealed that GTAs experienced challenges with a) online instruction, b) students, and c) personal challenges. Also, GTAs encountered conflicts regarding a) safety concerns and precautions and b) online-related proficiency, support, and expectations. Lastly, GTAs a) employed empathy and flexibility, and b) created boundaries and consulted others as conflict management strategies. Findings are discussed and theoretical and practical implications are advanced.